Economic thoughts on the potential implications of COVID‐19 on the Canadian dairy and poultry sectors. (6th May 2020) - Weersink, Alfons; von Massow, Mike; McDougall, Brendan
Abstract: The dumping of milk, the offering of hospitality size goods in grocery stores, and the closure of processing facilities are examples of the disruptions caused by the pandemic to the dairy, poultry, and egg sectors. These supply management sectors, however, are more resilient to the impacts of COVID‐19 than other sectors as producers are generally more financially stable, losses are pooled, and production/marketing efforts are coordinated. Abstrait: Le déversement de lait, l'offre de produits grand format dans les épiceries et la fermeture des installations de transformation sont des exemples des perturbations causées par la pandémie dans les secteurs des produits laitiers, de la volaille et des œufs. Ces secteurs sous gestion de l'offre, cependant, résistent mieux aux impacts du COVID‐19 que d'autres secteurs, car les producteurs sont généralement plus stables financièrement, les pertes sont partagées sur l'ensemble et les efforts de production/commercialisation sont coordonnés.